2019
DOI: 10.1039/c9ta07652b
|View full text |Cite
|
Sign up to set email alerts
|

Electronic reconfiguration of Co2P induced by Cu doping enhancing oxygen reduction reaction activity in zinc–air batteries

Abstract: Cu-Doped Co2P nanoparticles anchored on 2D heteroatom-doped ultrathin carbon exhibit excellent oxygen reduction reaction performance in flexible solid state zinc–air batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 56 publications
1
39
0
Order By: Relevance
“…3 b, c), Fe and Cu, can be doped on active substrate materials, such as carbon materials (graphene, CNTs, etc.). It has also been confirmed that 2D heteroatoms exhibiting unique structures and physical and chemical properties, such as N, P, S [ 22 , 48 ] and B [ 49 54 ] (as shown in Fig. 3 d, e), can improve the electrochemical and electrocatalytic performances of the catalysts.…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…3 b, c), Fe and Cu, can be doped on active substrate materials, such as carbon materials (graphene, CNTs, etc.). It has also been confirmed that 2D heteroatoms exhibiting unique structures and physical and chemical properties, such as N, P, S [ 22 , 48 ] and B [ 49 54 ] (as shown in Fig. 3 d, e), can improve the electrochemical and electrocatalytic performances of the catalysts.…”
Section: Introductionmentioning
confidence: 80%
“…The most typical strategy to optimize the catalyst performance is to combine heteroatom-doped carbon nanomaterials with transition metal-based material (oxides, chalcogenides such as Ni-based sulfides, etc. [ 19 21 ], transition metal phosphides (TMP [ 22 ]) and nitride) composites. As ZABs electrocatalysts still have numerous shortcomings, it is vital to optimize their catalytic structure.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations